Influence of working conditions on German paramedics' intention to leave the profession: a cross-sectional study - Thomas Hofmann; Thomas Hofmann; Thomas Hofmann; Michael Stanley; Michael Stanley; Luis Möckel (Frontiers in Health Services)
IntroductionIt is well known that Germany's ambulance service (AS) suffers from a shortage of qualified personnel, which may increase in the following years. For this reason, this study aimed to determine the percentage of AS staff considering leaving their profession and to analyse the possible causes.MethodsA self-developed questionnaire and the Employee Experience Questionnaire (EXQ) were used for this cross-sectional study.ResultsA total of 814 AS staff with a mean age of 35.71 [standard deviation (SD) 9.78] years were included in this study. Immediately leaving the AS was the intention of 17.27% of participants, with 2.86% having already resigned, 14.29% taking actions such as applying for a job, and another 14.04% specifically planning to leave the AS in the foreseeable future. Those who plan to leave the AS immediately [3.82 (SD 0.79)] showed significantly lower EXQ scores than the group who plan to stay in the EMS until retirement [4.92 (SD 0.87); pTukey ≤0.001]. At the same time, it is noticeable that EMS staff often suffer from unfavourable working conditions, such as not being granted breaks, work-related calls during free time, and over time, and significant correlations with the planned length of stay in the paramedic service and exit thoughts were identified here.ConclusionUnfavourable working conditions further aggravate the already existing shortage of qualified personnel in the ambulance service, so measures by various decision-makers are imperative.